Psychological factors of the transfer of control in an automated vehicle - Odachowska Ewa; Ucińska Monika; Kruszewski Mikołaj; Gąsiorek Kamila (Open Engineering, 2021)
In accordance with the requirements of the NHTSA guidelines on Level 3 automation, the comfortable control transition times is about 40 seconds. The data obtained so far are consistent with the assumption that the situation is better when drivers receive a warning about critical events than when they have to take over control unexpectedly. How these variables are shaped in the presence of distractors and what influences psychological factors have on these aspects remains unknown. For this purpose, a research experiment was developed in which control was taken over when the driver was additionally forced to perform the indicated activity (e.g. by looking away from the road), or when road conditions made it impossible to focus on the road. Psychological (temperament) and psychomotor variables (reaction time, hand–eye coordination) were controlled. The study was conducted on active road traffic participant drivers (N=95). Not only the time of taking control was analyzed, but also the way that may have a significant impact on road safety. The results revealed a significant influence of distractors on the manner control is taken over. In the conditions without distractors, the subjects were more likely to take over control than to cause automatic braking.